Extensive Q-factor tuning for leaky modes with minimal frequency variation in asymmetric slab grating structures - Hyeon Sang Bark; Seong-Han Kim; Young Bin Ji; Jae Gwang Kwon; Chul Kang; In Hyung Baek; Kitae Lee; Seung Jae Oh; Tae-In Jeon; Chul-Sik Kee (Scientific Reports)
Abstract We investigated an asymmetric slab grating structure to achieve significant tuning of the quality (Q) factor for a leaky mode while minimizing frequency variation. This structure comprises two identical gratings placed on the top and bottom of a slab waveguide, with one grating laterally shifted to introduce asymmetry. Simulations demonstrate that lateral shifting of one grating induces extensive changes in the Q-factor with minimal frequency variation, particularly near the band-flip filling fraction because the band-flip filling fraction remains unaffected by the shifting. The independence of the band-flip filling fraction from lateral shifting is attributed to the superposition property of Bragg scattering processes in the asymmetric grating structure. Experimental verification in the terahertz range confirms significant control over the Q-factor of the leaky mode of the structure. The proposed asymmetric slab grating structure offers possibilities for mechanically controllable optical devices, which are applicable to tunable filters and sensors. This study advances our understanding and application of leaky modes in asymmetric grating structures, revealing a previously unexplored aspect of asymmetric optical lattice.